TechTip: AGIS - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Suppose you are an extension officer and you need information about the boundaries of a farm or on the soil properties in a particular district - life would be a lot easier if you could retrieve these data at will.